The microcredit study in Bolivia and Colombia Mexico (2014)
His paper presents an overview of scientific research applied to micro-credit in relation to the behavior of this in parts of Latin America as they are in Colombia, Bolivia and Mexico and alternative solution to the problem of poverty in the countries mentioned above.